Particles in Northern Athapaskan Languages - Pepper, Mary (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1993)
AbstractParticles in Athapaskan languages have discourse and syntactic functions. This paper will look at a sample of particles which have these functions, and attempt to answer two questions: 1) What is the primary translation and the secondary translation for each panicle; 2) If speech is stripped of particles, is it still considered "fluent" speech?